Tropical green roof maintenance best practice for high-rise residential buildings / Shafikah Saharuddin - Saharuddin, Shafikah (2018)
Numerous approaches towards sustainable development exist in order to overcome crucial environmental issues, including urban heat island, air pollution and lack of green spaces. One of the sustainable approaches to help minimizing this problem is by using the means of vegetation or plant material on rooftops or known as the green roof. Among the benefits of the green roof includes a good stormwater management, improves air quality, reduces the consumption of energy in the building, and provides new amenity spaces for the occupants. Regardless of the benefits of green roofs implementation, challenges in terms of its maintenance should also be taken into account and given attention. Moreover, the Eleventh Malaysia Plan (2_016-2020) is moving towards the green growth for sustainability and resilience to develop a green environment and culture. Unfortunately, the maintenance management of green roof is often being neglected and unprioritised during the planning stage of its implementation. Among the major problems of maintaining green roof in residential are higher maintenance cost, involves a complicated and tedious process, and there is no standard maintenance system established for the green roof in the Malaysian context. Hence, the research is aimed to establish maintenance best practice of green roof for high-rise residential, with criteria identification and ranking. The objectives of this study are to identify the criteria of green roof maintenance, to rank the maintenance criteria of green roof practice, and lastly to establish the best practice of maintenance for the green roof in high-rise residential buildings. A mixed-method approach was used in this study, where both quantitative and qualitative data was utilised in the methodology phases